2016
DOI: 10.1016/j.foodres.2016.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic-loaded microcapsule system for human in situ folate production: Encapsulation and system validation

Abstract: This study focused on the use of a new system, an alginate|Ɛ-poly-l-lysine|alginate|chitosan microcapsule (APACM), able to immobilize a folate-producing probiotic, Lactococcus lactis ssp. cremoris (LLC), which provides a new approach to the utilization of capsules and probiotics for in situ production of vitamins. LLC is able to produce 95.25±26μg·L of folate, during 10h, and was encapsulated in the APACM. APACM proved its capacity to protect LLC against the harsh conditions of a simulated digestion maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…These results confirmed that the gastric conditions are particularly stressful for microorganisms. 20,26,49,50 In fact, the acidic environment of the stomach could be responsible for the damage of the cell membrane, DNA and cellular proteins leading to the loss of bacterial viability. 51,52 Different results were obtained upon digestion of MG-gels.…”
Section: Food and Function Papermentioning
confidence: 99%
“…These results confirmed that the gastric conditions are particularly stressful for microorganisms. 20,26,49,50 In fact, the acidic environment of the stomach could be responsible for the damage of the cell membrane, DNA and cellular proteins leading to the loss of bacterial viability. 51,52 Different results were obtained upon digestion of MG-gels.…”
Section: Food and Function Papermentioning
confidence: 99%
“…In the oral phase, survival rates showed no significant decrease in all treatment groups (0.74-1. to 10 CFU/ml after incubation in simulated gastric juice (pH 2) for 2 and 1 h, respectively, whereas more than 80% Al/Chi-encapsulated cells survived under these conditions [26]. L. lactis encapsulated with alginate-chitosan also showed high viability (75.0%) upon exposure to gastric condition for 2 h, whereas the number of free cells was less than 1 log within 90 min of treatment [27]. Free B. breve were undetected in the presence of gastric condition (pH 2) for 60 min, while the viability of Al/Chi-encapsulated cells (76.8%) further improved [6].…”
Section: Survival Of the Encapsulated L Acidophilus Under Simulated mentioning
confidence: 96%
“…Sequential digestion was adapted from Ramos et al (2016) with slight modifications. To evaluate the survivability of LGG under simulated gastrointestinal condition, 1 g of capsules or 1 mL of free cells were added to 9 mL of sterile simulated gastric juice (SGJ: 7 mL/L 0.1 M HCl, 2 g/L NaCl, 3.2 g/L pepsin) at pH 2.0 and incubated at 37 °C for 0 -2 h (with interval of 1 h) with constant agitation at 100 rpm.…”
Section: Sequential Digestionmentioning
confidence: 99%